Islamic Ethics and Modern Governance: The Case of Mental Revolution in Papua’s Religious Affairs Office - Luhuringbudi, Teguh; Yahya Komarudin; Mowafg Abrahm Masuwd; Massuhartono; Alhusni; M. Zaki (Pusat Kajian Moderasi Beragama dan Ideologi Pancasila UIN Sulthan Thaha Saifuddin Jambi, 2025)
The present study demonstrated that the